Effectiveness of Intramuscular Diclofenac Sodium Injection versus Diclofenac Suppositories in Post- Operative pain management in Inguinal Hernia - Sidra Aleem, Naeem Sarwar, Sajida Naseem, Muhammad Arshad Abbas, Sohail Hameed, Asra Aleem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This study was conducted to compare the route of administration of diclofenac intramuscular and suppository to see which one of these has more effectiveness. Aim: To compare intramuscular diclofenac sodium Injection with diclofenac suppositories in post operative pain management in patients with Inguinal Hernia. Study design: Randomized controlled trial and non probability consecutive sampling Methods: In this study 150 male cases accompanying age range of 18 to 60 age bearing unintended inguinal split were contained. They were detached into two equal groups and were trained accompanying subcutaneous injection of diclofenac sodium and those camp accompanying diclofenac suppositories. Post functioning pain was evaluated at 6, 12 and 24 hours on optic parallel scale (VAS). Results: In this study there were about up to 150 patients, 75 in each bunch and all were male. The average age in gather A and B was 43.50±5.72 vs 44.16±5.31 a long time individually. There were 47(62.67%) proficient in bunch A and 50(66.67%) in gather B. There were 58 cases each in both bunches having history of smoking. Require for protect absence of pain in bunch A was seen in 28 (37.33%) and in gather B in 19(25.33%) cases. Mean torment score on VAS at 6 hours was 2.39±0.84 vs 2.20±0.90 with p=0.64, at 12 hours it was 2.33±0.89 vs 2.11±0.94 with p= 0.94 and at 24 hours it was 2.03±0.71 vs 1.85±0.89 with p= 0.001. Conclusion: Post operative pain is one of the major concerns and Diclofenac suppositories have shown significantly better results at 24 hours as compared to intramuscular injections; though no statistical difference was observed at 6 and 12 hours. And this difference is also significant in terms of all the study variables at 24 hours in suppository group.